Chronic Urinary Infection in Overactive Bladder Syndrome: A Prospective, Blinded Case Control Study - Khan, Zainab; Healey, Gareth D.; Paravati, Roberta; Berry, Nidhika; Rees, Eugene; Margarit, Lavinia; Gonzalez, Deyarina; Emery, Simon; Conlan, Robert Steven (Frontiers in Cellular and Infection Microbiology, 2021)
Objectives To investigate whether women with overactive bladder (OAB) symptoms and no evidence of clinical infection by conventional clean-catch midstream urine cultures have alternative indicators of sub-clinical infection. Patients/subjects, materials & methods The study was a prospective, blinded case-control study with 147 participants recruited, including 73 OAB patients and 74 controls. The OAB group comprised female patients of at least 18 years of age who presented with OAB symptoms for more than 3 months. Clean-catch midstream urine samples were examined for pyuria by microscopy; subjected to routine and enhanced microbiological cultures and examined for the presence of 10 different cytokines, chemokines, and prostaglandins by ELISA. Results The mean age and BMI of participants in both groups were similar. No significant difference in the number of women with pyuria was observed between OAB and control groups (p = 0.651). Routine laboratory cultures were positive in three (4%) of women in the OAB group, whereas the enhanced cultures isolated bacteria in 17 (23.2%) of the OAB patients. In the control group, no positive cultures were observed using routine laboratory cultures, whereas enhanced culture isolated bacteria in 8 (10.8%) patients. No significant differences were observed in the concentrations of PGE2, PGF2α, MCP-1, sCD40L, MIP-1β, IL12p70/p40, IL12/IL-23p40, IL-5, EGF and GRO-α between the OAB and control groups. Conclusions Patients with OAB symptoms have significant bacterial growth on enhanced culture of the urine, which is often not detectable through routine culture, suggesting a subclinical infection. Enhanced culture techniques should therefore be used routinely for the effective diagnosis and management of OAB.